The poverty and survival strategy of sugar cane plantation laborers in Bondowoso - Jannah, M; Suharso, P; Sukidin (IOP conference series. Earth and environmental science, 2020)
This study aims to describe the poverty and survival strategies of sugar cane plantation laborers in Bondowoso. Descriptive qualitative research methodwas used to describe the poverty conditions of sugar cane plantation laborers in Bondowoso and the survival strategies of the laborers. The method used to determine the subject was the snowball method. Data collection methods used were interviews. Qualitative data analysis was used a data analysis method. The results of this study indicate the poverty of sugar cane plantation communities in Bondowoso was related to the dependence of laborers on landowners. Sugar cane plantation laborers in Bondowoso were able to fulfill their daily needs with various survival strategies. The most dominant survival strategy was to do worked as a worker in the fields who requires of labor and become cattle breeders of others. Suggestions were given to the Bondowoso local government to pay more attention to the welfare of sugar cane plantation laborers, expand employment and increase economic potential in the area around sugar cane plantations by developing sugar-based commodity industries, so as to absorb labor from sugar cane plantation laborers and increase their income.